John Ruskin’s word paintings in the context of his principle of clear vision as well as the biblical and rhetorical tradition - Piasecka, Aleksandra (Journal of Education Culture and Society, 2020)
This paper focuses on the chosen ekphrases (i.e. literary descriptions of visual works of art) which can be found on the pages of the treatises on painting and architecture written by John Ruskin, one of the most influential Victorian critics. However, these detailed and suggestive passages did not only serve the complementary purpose of illustrating the train of thought of the art connoisseur who was sharing his impressions from the continental tour with the readers. The style of word paintings also owes much to Ruskin’s intended lesson in astute observation, regarded as a necessary precondition to understanding the world, and his self-appointed function as a moralist who foresaw the danger of the spiritual decline looming over England. For this reason, first the critic’s notions of truth and nature will be discussed to elucidate the importance of clear perception in Ruskin’s writings. Then the ekphrases will be analyzed, paying special attention to their language which reveals the roles assumed by the critic. Simultaneously, references to the sources of Ruskin’s style, the Bible and ancient rhetoric, will have to be made.